Influence of the ion implantation on the electroabsorption spectrum in the photorefractive GaAs/AlGaAs quantum wells - Miśkiewicz, Eliza Magdalena; Wichtowski, Marek; Weinert-Rączka, Ewa (Photonics Letters of Poland, 2016)
Dark resistivity and electrooptic effect are two of the necessary conditions crucial for the photorefractive effect to occur. Proton implantation used for increasing the dark resistivity of semiconductor heterostructures can influence the electrooptic coefficient. In this paper, there are presented the results of absorption and electroabsorption spectra measurements in semi-insulating GaAs/Al0.3Ga0.7As multiple quantum well (MQW) structures. The dependence was analyzed between the electroabsorption amplitude near the excitonic peaks and the different proton implantation parameters. Full Text: PDF References P. Yeh, Introduction to photorefractive nonlinear optics (New York, Wiley & Sons 1993). CrossRef M. Carrascosa, F. Agulló-Rueda, F. Agulló-Lopez, "Steady holographic gratings in semiconductor multiple quantum wells", Appl. Phys. A 55, 25 (1992). CrossRef D.D. Nolte, "Dynamic holographic phase gratings in multiple-quantum-well asymmetric Fabry–Perot reflection modulators", Opt. Lett. 19(11), 819 (1994). CrossRef P. LiKamWa, A.M. Kan’an, "Ultrafast all-optical switching in multiple-quantum-well Y-junction waveguides at the band gap resonance", IEEE J. Selected Topics in Quantum Electronics 2(3), 655 (1996). CrossRef A. Ziółkowski, "Temporal analysis of solitons in photorefractive semiconductors", J. Opt. 14(3), 035202 (2012). CrossRef A. Ziółkowski, "Self-bending of light in photorefractive semiconductors with hot-electron effect", Opt. Express 22 (4), 4599 (2014). CrossRef Q. Wang, R.M. Brubaker, D.D. Nolte, M.R. Melloch, "Photorefractive quantum wells: transverse Franz–Keldysh geometry", J. Opt. Doc. Am. B 9 1626 (1992). CrossRef Q. Wang, D.D. Nolte, M.R. Melloch, "Two-wave mixing in photorefractive AlGaAs/GaAs quantum wells", Appl. Phys. Lett. 59 256 (1991). CrossRef S. Balasubramanian, I. Lahiri, Y.Ding, M.R. Melloch, D.D. Nolte, "Two-wave-mixing dynamics and nonlinear hot-electron transport in transverse-geometry photorefractive quantum wells studied by moving gratings", Appl. Phys. B 68, 863 (1999). CrossRef